Rethinking immunization programs through the life course approach - Balsells, Evelyn; Ghiselli, Margherita; Hommes, Carolina; Nascimento Lins de Oliveira, Beatriz; Rosado-Valenzuela, Ana Lucía; Vega, Enrique (Frontiers in Public Health, 2024)
The world continues to undergo a profound demographic shift towards increasing longevity -but quality of life is not improving correspondingly. At the same time, countries are taking stock of the negative impacts of the COVID-19 pandemic on national immunization programs. The pandemic exacerbated the declines in vaccination coverage for multiple vaccine-preventable diseases (VPD). To ensure that all persons receive all the vaccines for which they are eligible, it is time to consider how applying a life course approach (LCA) to immunization programs can help reinvigorate and redesign actions for greater vaccine uptake. In this mini review, we present the key concepts and principles of the LCA as applied to national immunization programs. Also, we offer recommendations on how health systems can achieve regional and national goals to ensure all people receive the recommended vaccine doses at every stage of life, thus ensuring the greatest benefits for individuals and societies.